2010 sonrası Türkiye sinemasında annelik - Övüç, Zümrüt (My University, 2019)
Eril düzen içinde genelde kadının, özelde annenin konumunu, görevlerini ve temsilini sunmada önemli bir yere sahip olan sinema, eril bakış açısı ile şekillenmekte, düzenin devamını öngören kalıplaşmış özellikler üzerine inşa edilmektedir. Bu düzenin temel dinamiklerinden birini oluşturan “annelik” ise, genelde sorgulanmaya imkan tanımayan, kutsallık halesi altında, ailesi ve özellikle çocukları için kendisini adayan bir figür olarak yer bulmakta, bu özveriye sahip olmayan ya da bu kalıpların dışına çıkan anneler ise sinemasal evrenin eril düşleminde “kötü” anne olarak sunulmaktadır. Bu çalışmanın amacı ise genel anlamda anneliğe atfedilen özelliklere, kültürel çalışmalar ekseninde yer vererek, bu atfın temel izleğini sorgulamakdır. Zira annelik, anaerkil düzen içinde en önemli konumu ifade ederken, eril erkin iktidarı ele geçirmesiyle, annenin “yeniden üretme” ya da var etme edimi, kültür evrenini yaratan erkeğin lehinde değişim geçirerek, annelik sadece kadının “fizyolojik kaderi” haline getirilmiştir. Bu kader ise, eril düşünce merkezinde görev bilinci yüksek annelik kavramıyla anne aleyhinde şekillendirilmiştir. Bu çalışma kapsamında ele alınan ve 2010 sonrası Türkiye Sineması’nda üretilen bağımsız sinema örnekleri içinde merkezine annelik kavramını ve deneyimini alan kadın yönetmeler tarafından üretilen Zefir (2010), Köksüz (2013) ve Ana Yurdu (2015) filmleri ise dişil perspektiften anneliğin kusurlu, marazlı yanına dikkat çekerek, eril söylemin anne için öngördüğü kalıpları sorgulamaya kapı aralamaktadır.

In the masculine order, cinema which has an important place in presenting the position, duties and representation of the woman in general and the mother in particular, is shaped from the masculine perspective and built on the stereotyped features that envision the continuation of the masculine order. Motherhood, which constitutes one of the basic dynamics of this masculine order, is generally found as a figure that does not allow any questioning and is devoted to her family and especially her children under the halo of holiness. Mothers who do not have this sacrifice or go beyond these patterns are presented as “bad” mother in the masculine phantasy of the cinematic universe. The aim of this study is to include the characteristics attributed to motherhood in the general sense in the axis of cultural studies and to question the basic traces of this attribution. Maternity refers to the most important position within the matriarchal order. But when the masculine power seizes power, the mother's ability to “reproduce” or act of generate has changed in favor of the man who created the cultural universe, and motherhood has only become the “physiological fate” of the woman. This fate is shaped against the mother with the concept of high motherhood in the masculine order. In this study, Zefir (2010), Köksüz (2013) Ana Yurdu (2015) films produced by female directors are included. These films, which produced after 2010 and are examples of independent cinema in Turkey, center on the concept and experience of motherhood and draw attention to the imperfect, morbid side of motherhood from the feminine perspective and open the door to questioning the patterns that masculine discourse predicts for the mother.
Keywords: Annelik; Female Director; Feminist Film Kuramı; Feminist Film Theory; Kadın Sineması Motherhood; Motion pictures; Psikanaliz; Psychoanalysis; Sinema; Turkey; Türkiye; Woman’s Cinema